Analysis of Dryness Effect on Skin by Adapting Hyperelastic Constitutive Model / Nor Fazli Adull Manan ...[et al.] - Adull Manan, Nor Fazli; Abdul Aziz, Abdul Hakeem; Mahmud, Jamaluddin; Abdullah, Abdul Halim (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The El Nino phenomenon can damage the skin and cause sickness such as skin cancer, heat stroke and heat exhaustion. Due to this phenomenon, an analysis on mechanical properties on animal skin is carried out, where sheepskin is used for investigation through uniaxial tensile test. The aim of this study is to investigate the effect of varied temperature on mechanical properties of animal skin. The process consists of an integration between experimental and numerical approach. A uniaxial tensile test is performed first to measure the basic mechanical parameter of stress-stretch by following the ASTM D2209-00 International testing standard. Next, the hyperelastic constitutive model Arruda and Boyce (A&B) equation is simplified via numerical approach for finding the material parameter. Then, a graph of Stress - Stretch (σ-λ) is plotted for a curve fit with the experimental data to obtain the mechanical properties of the material parameter. As a result, the material parameter which are Arruda and Boyce coefficient, μ and Arruda and Boyce exponent, N are 4.967(MPa) and 3.116, respectively, for SL Temp 33. However, μ and N for SNL Temp 33 are 5.134 (MPa) and 2.357. In contrast, the value of the value of μ and N for SL Temp 36 are 4.943(MPa) and 2.728 and for SNL Temp 36 are 5.199(MPa) and 2.209 .Therefore, this study could be useful for future studies in analysis of skin by adapting hyperelastic constitutive model.